Leading-Edge Velocities and Lifted Methane Jet Flame Stability - Wang, W.; Lyons, K. M. (Journal of Combustion, 2010)
Current interest exists in understanding reaction-zone dynamics and mechanisms with respect to how they counterpropagate against incoming reactants. Images of flame position and flow-field morphology are presented from flame chemiluminescence and particle image velocimetry (PIV) measurements. In the present study, PIV experiments were carried out to measure the methane jet lifted-flame flow-field velocities in the vicinity of the flame leading edge. Specifically, velocity fields within the high-temperature zone were examined in detail, which complements previous studies, whose prime focus is the flow-field upstream of the high-temperature boundary. PIV data is used not only to determine the velocities, but, along with chemiluminescence images, to also indicate the approximate location of the reaction zone (further supported by/through the leading-edge flame velocity distributions). The velocity results indirectly support the concept that the flame is anchored primarily through the mechanism of partially premixed flame propagation.